Financial accounting - Libby, Robert; Short, Daniel G.; Libby, Patricia A. (Boston : Irwin/McGraw-Hill, 1998)
Based on real company annual reports, this volume concentrates on financial accounting. It discusses cash flows, statements of cash flows, and the impact various accounting transactions have on business decisions.
Includes bibliographical references and index.
oif 11/03/15
Loan
Keywords: Corporations -- Accounting; Accounting; Financial statements